Analisa Perancangan Dan Penggunaan Sistem Pembelian Token Listrik Dengan Memanfaatkan Pulsa Sms Melalui Smartphone - Owen Gloria Tjandrawan Laza (International Journal Labs, 2022)
electric power to operate it, such as lights, washing machines, water pump machines, televisions, radios, computers and other electronic devices. Electricity is a very important human need for everyday life that makes humans very dependent on electricity, designing a system for purchasing electricity tokens by utilizing SMS pulses via smartphones. This research was carried out by collecting materials from books, scientific works, or writings related to the problems discussed in the study, With this system it can make it easier for customers to fill electricity tokens automatically, namely so that customers do not have to go to electricity token sales kiosks, the process when checking the remaining credit quota sent by the system via wavecom, customers will receive a remaining quota warning if the quota is close to the minimum limit via SMS on the smartphone.